Pengalaman Perawat dalam Menghadapi Masa Persiapan Pensiun di RS Bhayangkara Denpasar - Tri Astuti wira Pratiwi; Ni Komang Sukraandini; Putu Gede Subhaktiyasa (Jurnal Akademika Baiturrahim Jambi, 2020)
Retirement is a separation from employment whereby an employee opts to cease working due to age or disability. Retirement preparation is a set of plan for employees to adapt to some challenges for their retirement. This study aimed at analyzing nurses’ experiences towards retirement preparation. To accomplish this goal, this study used a descriptive qualitative design which was descriptive phenomenological approach. This study was conducted in 2019 in Bhayangkara Hospital Denpasar. The sample of this study was 4 participants. The technique used was purposive sampling. The data were collected through in-depth interview and field notes. The obtained data were analyzing through colaizi method. The results of this study were  4 themes such as, 1. nurses’ understanding towards retirement preparation,  2. nurses’ feelings towards retirement preparation, 3. the challenges faced by nurses towards retirement preparation, 4. ways to cope with challenges of retirement preparation. Researcher expectations For nurses who will retire can improve the ability and service of nurses in dealing with problems experienced by clients